Acute Toxicity of 70% Ethanol Extract of Kenitu (Chrysophyllum cainito L.) Leaves of Wistar Rats (Rattus norvegicus) - Maulina, Novia; Fawzia, Rachma Izza; Firdausy, Alif Firman; Quintão, Roberto Doutel; Ma'arif, Burhan (Journal of Islamic Pharmacy, 2024)
The postmenopausal phase, which results in a lack of estrogen levels and is one of the triggers of menopausal symptoms, contributes to the elderly's cognitive function decline. This condition can also cause joint and bone pain, bladder and urinary tract disorders, and sexual problems. Based on several studies, it is known that kenitu (Chrysophyllum cainito L.) contains phytoestrogen compounds with a structure similar to the hormone estrogen, so kenitu has the potential as an alternative treatment for disease conditions with risk factors for estrogen deficiency. The study was conducted to determine the estimated lethal dose 50 (LD50) value based on the Globally Harmonized System (GHS) classification as well as macroscopic (physical, behavioral, and average weight gain per day) and microscopic (liver and kidney histology) values in Wistar rats against the administration of 70% ethanol extract of kenitu leaves at a dose of 2000 mg/kg body weight (BW). The Up-and-Down Procedure (UDP) acute toxicity test method was used for this study. The maximum dose was 2000 mg/kg BW of ethanol extract from 70% kenitu leaves. The study found that the 70% ethanol extract of kenitu leaves had more than 2000 mg/kg BW LD50 value against Wistar rats. Based on the classification of the GHS, it can be concluded that 70% ethanol extract of kenitu leaves against Wistar rats is classified as low toxicity.